PENGELOLAAN PENGOLAHAN SAMPAH ORGANIK DAN LINDI DI TPST DESA TULANGAN SIDOARJO - Atik Widiyanti; Yanuar Risah Prayogi Prayogi; Elsa Rosyidah; Laily Noer Hamidah; Ardhana Rahmayanti; Awang Andhika (Journal of Science and Social Development, 2020)
Tulangan Village is one of the villages located in Tulangan District, Sidoarjo Regency, East Java. The total population in Tulangan Village is 4818 people. So it is estimated that the average population of Tulangan Village produces more than 1,445.4 kg of waste / day. Currently, the TPST of Tulangan Village serves waste management for all residents of Tulangan Village. Until now, organic waste processing at TPST is carried out by composting. Meanwhile, leachate processing is only carried out by simple storage. To overcome this problem, the activities carried out are training in organic waste and leachate processing. Based on the results of the questionnaire, it was found that seven residents understood organic waste processing and seven people understood leachate processing.